Single‐Cell Nanoencapsulation of Saccharomyces cerevisiae by Cytocompatible Layer‐by‐Layer Assembly of Eggshell Membrane Hydrolysate and Tannic Acid. Issue 1 (15th January 2021) - Han, Sang Yeong; Lee, Hojae; Nguyen, Duc Tai; Yun, Gyeongwon; Kim, Seulbi; Park, Ji Hun; Choi, Insung S.
Abstract : Single‐Cell Nanoencapsulation In article number 2000037, Ji Hun Park, Insung S. Choi, and co‐workers